Composition and influencing factors of professionals' capacity in public health emergency rescues: a qualitative study - Fangfang Zhong; Yin Lin; Ying Chen; Yazhuo Gao; Xuehua Zhu (Frontiers Media S.A., 2024)
ObjectiveTo explore the composition and influencing factors of professionals' capacity in public health emergency rescues.MethodsA descriptive qualitative design was used in this study. Medical workers, managers, and members of an emergency rescue team in Hangzhou, Zhejiang, were recruited for participation through a purposive sampling method. The data were collected using semi-structured interviews and analyzed using a conventional content analysis method.FindingsA total of 2 themes and 13 sub-themes emerged from the analysis: ability composition (knowledge reserve, early warning assessment, information reporting, emergency response, self-protection, personal ability, coordination and cooperation, health education) and influencing factors (educational background, region, experience, hospital level, human resources, and financial investment).ConclusionThese findings offer a basis for the construction of a related indicator system and provide a reference for relevant departments to further optimize their emergency education and training, strengthen their emergency drills, and improve their emergency rescue abilities. The findings indicate that it is necessary to pay attention to the construction of an emergency rescue team, adjust the ratio of personnel, improve their remuneration, and promote work enthusiasm to improve the emergency rescue ability of an organization.